Statistical optimization of floating pulsatile drug delivery system for chronotherapy of hypertension - Kshirsagar, Sanjay J; Patil, Shrikant V; Bhalekar, Mangesh R (International Journal of Pharmaceutical Investigation)
Introduction: A pulsatile drug delivery system is characterized by a lag time that is an interval of no drug release followed by rapid drug release. The purpose of this work was to develop hollow calcium alginate beads for floating pulsatile release of valsartan intended for chronopharmacotherapy. Floating pulsatile concept was applied to increase the gastric residence of the dosage form having lag phase followed by a burst release. Materials and Methods: To overcome the limitations of various approaches for imparting buoyancy, hollow/porous beads were prepared by simple process of acid-base reaction during ionotropic crosslinking by low viscosity sodium alginate and calcium chloride as a crosslinking agent. In this study, investigation of the functionality of the sodium alginate to predict lag time and drug release was statistically analyzed using the response surface methodology (RSM). RSM was employed for designing of the experiment, generation of mathematical models and optimization study. The chosen independent variables, i.e. sodium alginate and potassium bicarbonate were optimized with a 32full factorial design. Floating time and cumulative percentage drug release in 6 h were selected as responses. Results: Results revealed that both the independent variables are significant factors affecting drug release profile. A second-order polynomial equation fitted to the data was used to predict the responses in the optimal region. The optimized formulation prepared according to computer-determined levels provided a release profile, which was close to the predicted values. The floating beads obtained were porous (21-28% porosity), hollow with bulk density <1 and had Ft70 of 2–11 h. The floating beads provided expected two-phase release pattern with initial lag time during floating in acidic medium followed by rapid pulse release in phosphate buffer. Conclusion: The proposed mathematical model is found to be robust and accurate for optimization of time-lagged formulations for programmable pulsatile release of valsartan.
Keywords: Calcium alginate beads; chronopharmacotherapy; floating-pulsatile drug delivery; full factorial design; response surface methodology